DNA ligase III and DNA ligase IV carry out genetically distinct forms of end joining in human somatic cells - Oh, Sehyun (2014)
Ku-dependent C-NHEJ (classic non-homologous end joining) is the primary DNA EJing (end joining) repair pathway in mammals. Recently, an additional EJing repair pathway (A-NHEJ; alternative-NHEJ) has been described. Currently, the mechanism of A-NHEJ is obscure although a dependency on LIGIII (DNA ligase III) is often implicated. To test the requirement for LIGIII in A-NHEJ we constructed a LIGIII conditionally-null human cell line using gene targeting. Nuclear EJing activity appeared unaffected by a deficiency in LIGIII as, surprisingly, so were random gene targeting integration events. In contrast, LIGIII was required for mitochondrial function and this defined the gene’s essential activity. Human Ku:LIGIII and Ku:LIGIV (DNA ligase IV) double knockout cell lines, however, demonstrated that LIGIII is required for the enhanced A-NHEJ activity that is observed in Ku-deficient cells. Most unexpectedly, however, the majority of EJing events remained LIGIV-dependent. In conclusion, although human LIGIII has an essential function in mitochondrial maintenance, it is dispensable for most types of nuclear DSB repair, except for the A-NHEJ events that are normally suppressed by Ku. Moreover, we describe that a robust Ku-independent, LIGIV-dependent repair pathway exists in human somatic cells.